Leveraging administrative data for public health responses to child maltreatment in Europe: Insights from a scoping review of studies across multiple sectors - O'Leary, Donna; Græsholt-Knudsen, Troels; Lätsch, David; Lamela, Diogo; Nevriana, Alicia; Nurmatov, Ulugbek; Quantin, Catherine; Bailey, Grace; Griffiths, Lucy; Broadhurst, Karen; Cowley, Laura Elizabeth (International Journal of Population Data Science, 2025)
Objectives Analysis of administrative data has the potential to assist in the public health response to child maltreatment (CM). We conducted a scoping review to identify European studies (2010–2024) that used individual-level administrative data to study (CM). Methods We searched eight electronic databases in November 2023 for studies analyzing national or regional administrative datasets or linking multiple datasets. There were no restrictions on language, study design or sector. A grey literature search was added in October 2024. Two independent reviewers confirmed inclusion eligibility, with a third resolving discrepancies. Of 1,730 studies identified, 237 full texts were reviewed and 173 were included. Four team members extracted data using a customized form. Data were summarized to present preliminary findings on the geographical scope of studies, data sources, populations and CM types studied, methodologies used, data accessibility and availability. Results The majority of studies were conducted in England (71; 40%), followed by Wales (26; 14%) and Denmark (20; 11%). Nineteen studies were multi-country, with no studies from Eastern or Southern Europe, representing a gap in the literature. Most studies focused on a single sector (n=131; 76%) while others linked data from multiple sectors. Most studies explored children exposed to any CM (139; 81%), others explored physical abuse (n=17), adversity (n=3), medical diagnosis of abuse (n=1), specific combinations of abuse (n=3) and violence (1). Studies included Data Resource Profiles (n=16) and primary studies using a range of methodologies including cohort, cross-sectional and longitudinal study designs. The number of studies increased from 2010 to 2024, peaking in 2022. Few studies reported complete data access and governance information. Conclusions The benefits of administrative data for studying CM are seen in the range of studies identified across sectors and countries. The geographical scope of the studies indicates opportunities for further advancement including potential investment in data curation and infrastructure.